Factors related to smoking behaviour among adolescent girls - Holida, Siti Solihat; Lupianti, Meisya; Yuliana, Lia (JOURNAL OF Mental Health Concerns, 2026)
Background: Smoking behaviour among adolescent girls is a growing public health concern, influenced by peers, parental guidance, and social environment. These factors play a critical role in shaping norms and smoking habits. Purpose: To determine the factors related to smoking behavior among adolescent girls. Methods: A cross-sectional design was used with a total population of 76 female adolescents. Data were collected using a structured online questionnaire via Google Forms, measuring smoking behaviour and the influence of peers, parents, and social environment. Univariable analysis described respondent characteristics, while bivariate analysis using the Chi-square test examined the association between variables, with a significance level of p < 0.05. Results: The study found that 53.9% of respondents were active smokers. Bivariate analysis indicated that peer influence (p = 0.031) and social environment (p = 0.009) were significantly associated with smoking behaviour, whereas parental influence was not statistically significant (p = 0.131). Adolescents with influential peers and a permissive social environment were more likely to smoke. Conclusion: Smoking behaviour among female adolescents is significantly influenced by peers and social environment, while parental influence shows no significant association in this age group. Preventive interventions should focus on strengthening positive social influences and controlling environmental factors to reduce the risk of smoking among adolescent girls. Keywords: Adolescent Girls; Parental Influence; Peer Influence; Smoking Behaviour; Social Environment.